Uma estratégia experimental de ensino de geometria espacial para o ensino médio - Alves, Cláudia Raquel (Universidade Federal Rural do Semi-Árido, 2019)
The fact that Spatial Geometry has always been a content present in the documents that guide the teaching of mathematics and is also charged in the tests of ENEM, which is today the main form of access to higher education, fostered the search for a way of teaching that prioritizes the knowledge of the student's daily life. In this sense, the present work brings a didactical proposal as a strategy for the study of Spatial Geometry in High School. As a suggestion we will bring a proposal with classes designed for classroom application using alternative materials and based on some of the learning theories found in the literature. The experiment was done in two high school classes. In one class we use the traditional method, used the textbook, brush and whiteboard. In the other class, we applied the differentiated class proposal using practical classes and alternative materials found in the student's daily life. The verification of the results of the didactical proposal will be based on a questionnaire applied to both classes.
Keywords: Geometria Espacial; Proposta didática; Ensino Médio; Spatial geometry; Didactical proposal; High school; CIENCIAS EXATAS E DA TERRA::MATEMATICA